FAKTOR-FAKTOR YANG MEMPENGARUHI ANGKA RUJUKAN PASIEN PESERTA KARTU INDONESIA SEHAT (KIS) DI PUSKESMAS TANAH TINGGI KECAMATAN BINJAI TIMUR KOTA BINJAI TAHUN 2018 - ., Saprilliani; Ginting, Rapael; Girsang, Ermi (Jurnal Kesehatan Masyarakat dan Lingkungan Hidup, 2019)
Refferal of participant in Indonesian Health Card (KIS) based on the Indonesian Health Profile in 2016 as much as 65.424.687 (26%) for the non tuition recipients and 106.514.567 (41%) for the tuition recipients . Based on the quarter profil in Puskesmas Tanah Tinggi, the amounts of the public referenced KIS  member as much as 2.501 (42%) out of all the visitors each month (5918) in 2018. In a health center (Puskesmas), referral service achievement ideally was not more than 15% according to KIS standard. This kind of thing opposites with KIS program that should be able to maximizing the function of puskesmas. This research using analytical survey method with cross sectional design which is helping to explain how the influence of knowledge, attitudes officer, availability of infrastructure and the human resources in that clinic to inform about the referenced in Puskesmas Tanah Tinggi, District of Binjai Timur in 2018. The population in this study were whole societies who included in the KIS patients in Puskesmas Tanah Tinggi and 98 patients as the samples. The data collection is doing by the questionnaires and by using the chi-square test. The result of this study indicated that the variables were significantly influenced to referral number. The variables are knowledge variable (p = 0,000 <p = 0,05). the availability of facilities and infrastructure variable (p = 0,001 <p = 0,05). and and the human resources in that clinic to inform about the referenced (p= 0,000 <p= 0,05). While the variable which didn’t influenze to referral number, were the attitude of the officers (p= 0,174 >p =0,05). Advised to the chief and employees in Puskesmas Tanah Tinggi, District of Binjai Timur in order to pursue and improve their competence especially health service in accordance with the standards and mechanisms that have been established specifically reference section